Disclosing Sexual Victimization Online and In-Person: An Examination of Bisexual+ and Heterosexual Survivors - López Dujisin, Gabriela (Journal of interpersonal violence, 2024)
Bisexual+ (bisexual, pansexual, queer, attraction to more than one gender) people are at elevated risk for sexual victimization relative to their heterosexual counterparts. Disclosure of sexual victimization and social reactions received upon disclosure can play a major role in recovery following an assault. Using an online survey, the current study examined whether bisexual+ and heterosexual survivors of sexual victimization (N = 657) varied in disclosure of victimization, the type of disclosure (in-person vs. online via #MeToo), and receipt of various social reactions to disclosure in person and online. A chi-square test examined differences in disclosure and differences in types of disclosure (in-person only vs. MeToo across sexual identity). MANOVAS were used to examine whether in-person and online reactions varied across sexual identity. Bisexual+ survivors were more likely to disclose sexual victimization relative to heterosexual survivors. Among those who disclosed, bisexual+ survivors were more likely to disclose in person only whereas heterosexual survivors were more likely to disclose online via #MeToo. Whereas we did not find any significant differences for in-person reactions, we did find significant differences for online social reactions using #MeToo. Heterosexual survivors received higher turning against reactions (e.g., avoided talking to you or spending time with you) and more unsupportive acknowledgment relative to bisexual+ participants. Whereas bisexual+ participants received less turning against reactions and unsupportive acknowledgment during #MeToo/online disclosure, they were also less likely to disclose using #MeToo. Findings suggest that bisexual+ and heterosexual people vary in the way they disclose sexual victimization, and in how they are responded to when disclosing in person and online.